A revisit of PSR J1909−3744 with 15-yr high-precision timing. Issue 2 (30th September 2020) - Liu, K; Guillemot, L; Istrate, A G; Shao, L; Tauris, T M; Wex, N; Antoniadis, J; Chalumeau, A; Cognard, I; Desvignes, G; Freire, P C C; Kehl, M S; et al.
ABSTRACT: We report on a high-precision timing analysis and an astrophysical study of the binary millisecond pulsar, PSR J1909−3744, motivated by the accumulation of data with well improved quality over the past decade. Using 15 yr of observations with the Nançay Radio Telescope, we achieve a timing precision of approximately 100 ns. We verify our timing results by using both broad-band and sub-band template matching methods to create the pulse time-of-arrivals. Compared with previous studies, we improve the measurement precision of secular changes in orbital period and projected semimajor axis. We show that these variations are both dominated by the relative motion between the pulsar system and the Solar system barycentre. Additionally, we identified four possible solutions to the ascending node of the pulsar orbit, and measured a precise kinetic distance of the system. Using our timing measurements and published optical observations, we investigate the binary history of this system using the stellar evolution code mesa, and discuss solutions based on detailed WD cooling at the edge of the WD age dichotomy paradigm. We determine the 3D velocity of the system and show that it has been undergoing a highly eccentric orbit around the centre of our Galaxy. Furthermore, we set up a constraint over dipolar gravitational radiation with the system, which is complementary to previous studies given the mass of the pulsar. We also obtain a new limit on the parametrized post-Newtonian parameter, | α_1 | < 2.1 × 10 −5 at 95 per cent confidence level, which is fractionally better than previous best published value and achieved with a more concrete method.